Understanding tilapia mortalities and fish health management in Lake Volta: a systematic approach - Zornu, Jacob; Tavornpanich, Saraya; Brun, Edgar; van Zwieten, Paul A. M.; van de Leemput, Ingrid; Appenteng, Patrick; Anchirinah, Janet; Cudjoe, Kofitsyo S. (Frontiers in Sustainable Food Systems, 2023)
Unusual fish mortalities in aquaculture threaten global food security and carry significant socio-economic burdens. In 2018, Nile tilapia (Oreochromis niloticus) suffered unusual patterns of mortalities, attributed to disease-causing agents in Lake Volta cage aquaculture. In recent times, disease investigations have shifted from single to consideration of multiple factors to understand the puzzling range of causal risk factors. This study therefore aimed at expanding on tilapia mortality risk factors, while documenting fish health and Lake Volta management practices for sustainable aquaculture. We interviewed relevant aquaculture stakeholders operating on Lake Volta and conducted thematic analysis on their responses to map out mortality risk factors and management practices. The identified risk factors were conceptualized in established models of causation web and Social-Ecological System to explain the practical significance of the findings. The results showed that the risk factors of tilapia mortalities are a combination of pathogens and non-infectious factors mediated by weak law enforcement. The results further suggested mortality reinforcing mechanisms through the horizontal transmission of pathogens, namely, Streptococcus agalactiae and Infectious Spleen and Kidney Necrosis Virus. Moreover, the recognition of weak enforcement as a possible factor reinforcing human activities is a non-infectious route that can be deleterious to fish health. Health management practices comprised phytotherapy, vaccination, heat shock treatment, biological controls, and best husbandry practices. Lake management involves creating a waterfront buffer of 85.34 m, surveillance, and executing the framework guiding aquaculture development on the Lake. The findings are suggestive of complementary quantitative studies that augment the qualitative evidence herein. Such follow up studies can disclose precise mortality risk factors to inform policy directives and effective remedial strategies that can secure fish and lake health.